Representações do Brasil e do brasileiro no discurso do jornal espanhol El País no contexto Pré-Copa FIFA de 2014 - Barrere, Luana Lisboa (2017)
The discourse production made by the international media about the political scenario in Brazil has been at stake lately, due to the high sport event, which was taking place in the country, since the Confederation Cup, in 2013, and the World Cup, in 2014, until the Olympics Games, in 2016, which gave a wide visibility to the country overseas. This research aims to analyze opinion articles from the journal El País published between 2013 and 2014, in order observe the discursive structures present due to representations and stereotypes from Brazil and its citizens in the context of political manifestations in that period. For that, we are going to use the presumptions of Critical Discourse Analysis (CDA), specially the works made by Van Dijk (2008; 2012) based on dialogue with scholars from Social Science (BOURDIEU, 1989), Social Psychology (MOSCOVICI, 1978; 2004), Cultural Studies (HALL, 2000; 2011) and other authors which contribute to the constitution of a social-historical panorama of Brazil (ZWEIG, 2013; AGASSIZ, 1975; RAEDERS, 1988) etc., characterizing a multidisciplinary bias from the Linguistics. We found out on Critical Discourse Analysis (CDA) our approach, since, while critical-historical perspective has aim to examine the relations between discourse and power, this will allow us to argue a possible intergroup polarization among Europeans and Brazilians, and consequently, the (re) production of unfavorable representations of Brazil and Brazilians, the existence of a hierarchical relation among cultures, from the Spanish journalistic speech.